Le clinicien et la question de la « dangerosité » : à la croisée du social et de l’individuel - Bogopolsky, Yann (Criminologie, 1984)
The concept of “dangerosity” as applied to a single individual excludes other forms of social violence.I) A “mythical” function which names what appears threatening.II) An “instrumental” function which identifies the so-called Social Disease, legitimizes the violence of incarceration, and pursues the quest for a rationale.III) A “symbolic” function which points out dangerous individuals in order to set them apart.The clinician becomes a prisoner of that notion. As an expert he is forced by the judicial process to restrict the psychic reality down to the responsibility and irresponsibility levels. The play-then moves on from the social to the individual scene. Within the institution, he must tell fantasies and reality apart while at the same time — caught in the trap — he becomes the “watcher” of those excluded.Society asks the clinician to restore its image of a perfect world but when the penalty is applied, it seems likely that it can be traced back to the same drives.